STRESS AKADEMIK DAN KUALITAS TIDUR TERHADAP KESEJAHTERAAN SUBJEKTIF MAHASISWA DI MASA PANDEMI COVID-19 - Islam, Azizah Fajar; Mulamukti, Ajheng (Jurnal Ilmiah Penelitian Psikologi, 2021)
During the online learning process during the Covid-19 pandemic, various problems were found that made the learning process and understanding learning materials ineffective and a trigger for academic stress on students. Generally academic stress is followed by decreased sleep quality. High academic stress and poor sleep quality in students can reduce students' subjective well-being. The purpose of this study was to determine the relationship between academic stress and sleep quality with subjective well-being in students, especially UHAMKA students in online learning amidst Covid-19. This study uses quantitative research methods with correlational statistical analysis. A total of 347 respondents participated in this study. Based on the results of data analysis that has been done, that there is a significant negative relationship between academic stress and sleep quality with subjective well-being with correlation coefficient values "‹"‹of -0.555 and -0.226. That is, the lower the academic stress, the higher the subjective well-being and the higher the score of sleep quality, which means that the low quality of sleep encourages lower subjective well-being in students, and vice versa. In future research, it is expected to examine other variables such as resilience and motivation to see the condition of students after the Covid-19 virus outbreak is reduced.